The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1007/s12013-014-0280-2
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Epigallocatechin-3 Gallate on Atrial Electrical and Structural Remodeling in a Rabbit Rapid Atrial Pacing Model

Abstract: Epigallocatechin-3 gallate (EGCG) is the major catechin in green tea. The aim of this study is to investigate the effects of EGCG on atrial electrical and structural remodeling in a rabbit rapid atrial pacing (RAP) model. New Zealand white rabbits were subjected to RAP with or without EGCG treatment. The atrial electrophysiology was studied. ELISA, Western blots, and RT-PCR were performed to determine the level of the inflammation markers, oxidative stress, and fibrogenic agents. Atrial tissue was stained with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Our previous investigation reported that EGCG significantly suppresses the TNF-alpha-induced MCP-1 protein and mRNA expression, thereby inhibiting inflammation and anti-oxidative stress [27]. Zhu et al reported that EGCG protected against atrial electrical and structural remodeling in a rabbit RAP model by attenuating inflammation and oxidative stress [48]. Therefore, EGCG could be the most important contributor to the beneficial effect of green tea on AF incidence.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous investigation reported that EGCG significantly suppresses the TNF-alpha-induced MCP-1 protein and mRNA expression, thereby inhibiting inflammation and anti-oxidative stress [27]. Zhu et al reported that EGCG protected against atrial electrical and structural remodeling in a rabbit RAP model by attenuating inflammation and oxidative stress [48]. Therefore, EGCG could be the most important contributor to the beneficial effect of green tea on AF incidence.…”
Section: Discussionmentioning
confidence: 99%
“…The selective efficacy of EGCg towards ECs and SMCs could be attributed to its molecular structure, which includes a plethora of hydroxyl groups and galloyl group [ 60 ]. Effects of EGCg for their cardioprotective properties as well as for their efficacy as anti-atherosclerotic and anti-hypercholesterolemic characteristics have been explored in the past [ 61 , 62 ]. Our previous investigations related to the in vitro and vivo antitumor efficacy have demonstrated that EGCg conjugated onto AuNPs has better efficacy compared to the free EGCg due to the larger surface area of AuNPs [ 22 , 33 ].…”
Section: Discussionmentioning
confidence: 99%